Efficient formation of [3]pseudorotaxane based on cooperative complexation of dibenzo-24-crown-8 with diphenylviologen axle. Issue 62 (19th June 2020) - Sakata, Yoko; Ogura, Takaya; Akine, Shigehisa
Abstract : A novel cooperative [3]pseudorotaxane system consisting of dibenzo-24-crown-8 (DB24C8) and diphenylviologen axle has been developed. Abstract : A novel cooperative [3]pseudorotaxane system consisting of dibenzo-24-crown-8 (DB24C8) and diphenylviologen axle has been developed. The two-step formation of the [3]pseudorotaxane occurred in a positive-cooperative manner. The corresponding [3]rotaxane was successfully obtained from just a stoichiometric mixture of each component by end-capping without dissociation.